Woody Species Alpha‐diversity and Species Abundance Distributions in an African Semi‐deciduous Tropical Rain Forest. (4th June 2015) - Mwavu, Edward N.; Witkowski, Ed T. F.
Abstract Understanding plant species diversity patterns and distributions is critical for conserving and sustainably managing tropical rain forests of high conservation value. We analyzed the alpha‐diversity, species abundance distributions, and relative ecological importance of woody species in the Budongo Forest, a remnant forest of the Albertine Rift in Uganda. In 32 0.5‐ha plots, we recorded 269 species in 171 genera and 51 families with stems of ≥2.0 cm in diameter at breast height (dbh). There were 53 more species with stems of ≥2.0 cm dbh than with stems of ≥10 cm dbh, of which 33 were treelets and 20 were multi‐stemmed shrubs. For both minimum stem diameter cut‐offs (i.e., ≥2 cm dbh vs. ≥10 cm dbh), the Fabaceae, Euphorbiaceae, Ulmaceae, and Meliaceae families and the species Cynometra alexandri, Lasiodiscus mildbraedii, and Celtis mildbraedii had the highest relative ecological importance. The relative ecological importance of some species and families changed greatly with the minimum stem diameter measured. Alpha‐diversity, species richness, and species abundance distributions varied across historical management practice types, forest community types, and as a function of minimum stem diameter. Species richness and Shannon–Weiner diversity index were greater for species with stems of ≥2.0 cm dbh than of ≥10 cm dbh. The decrease in species evenness with an increasing number of plots was accompanied by an increase in species richness for trees of both minimum diameters. This forest is characterized by a small number of abundant species and a relatively large proportion of infrequent species, many of which are sparsely distributed and with restricted habitats. We recommend lowering the minimum stem diameter measured for woody species diversity studies in tropical forests from 10 cm dbh to 2 cm dbh to include a larger proportion of the species pool.